Resistance mechanisms to immune checkpoint inhibitors: updated insights - Besan H. Alsaafeen; Bassam R. Ali; Eyad Elkord (Molecular Cancer)
Abstract The last decade has witnessed unprecedented succusses with the use of immune checkpoint inhibitors in treating cancer. Nevertheless, the proportion of patients who respond favorably to the treatment remained rather modest, partially due to treatment resistance. This has fueled a wave of research into potential mechanisms of resistance to immune checkpoint inhibitors which can be classified into primary resistance or acquired resistance after an initial response. In the current review, we summarize what is known so far about the mechanisms of resistance in terms of being tumor-intrinsic or tumor-extrinsic taking into account the multimodal crosstalk between the tumor, immune system compartment and other host-related factors.